The Influence of Ice Breaking on The Motivation and Learning Outcomes of First Grade Students - Perawati Bte Abustang; Nurhadifah Amaliyah; Muh. Khaedar; Rosmiati (Universitas Pendidikan Ganesha, 2025)
Early grade Indonesian language learning continues to face challenges, particularly low student participation and learning achievement caused by the use of monotonous and less varied instructional methods. This study aims to analyze the effect of implementing ice breaking on improving students’ motivation and learning outcomes in first grade Indonesian language learning. The research employed a pre-experimental design with purposive sampling, involving first grade students as the study subjects. Data were collected through observation sheets, questionnaires, achievement tests, and documentation, while data analysis was conducted using descriptive statistics and a paired samples test through SPSS version 21. The findings indicate an increase in students’ motivation and learning outcomes after the implementation of ice breaking, as reflected in the shift of motivation categories from low in the pre-test to high and very high in the post test. Hypothesis testing showed a significance value of 0.000 < 0.05, confirming that ice breaking has a significant effect on learning outcomes. The study concludes that ice breaking is an innovative instructional strategy capable of creating a more active, enjoyable, and conducive learning environment, thereby positively influencing students’ motivation and academic achievement. The implications of this study highlight that ice breaking can be applied as a supportive approach in early-grade Indonesian language learning to strengthen students’ thinking processes, comprehension, and active participation.